A self-assembled, π-stacked complex as a finely-tunable magnetic aligner for biomolecular NMR applications1. Issue 13 (14th February 2015) - Sato, Sota; Takeuchi, Ryosuke; Yagi-Utsumi, Maho; Yamaguchi, Takumi; Yamaguchi, Yoshiki; Kato, Koichi; Fujita, Makoto
<x xml:space="preserve">Abstract</x> The 1D aggregates of π-stacked self-assembled complexes worked as magnetic aligners upon an analyte protein to observe RDC in NMR.